Isolation and identification of bacteria capable of sulfate reduction from palm oil sludge - Mirfasih, Noosha (2013)
Sulfur in its native is a yellow crystalline solid. In nature, it occurs as the pure element or as sulfide and sulfate minerals. Inorganic sulfur compounds can be found in the form of sulfate, sulfide, sulfite, thiosulfate, elemental sulfur and polythionates. Sulfate appears to be the most stable and abundant form of sulfur available for use by living organism in the biosphere. This present study focused on the isolation and identification of bacteria capable of sulfate reduction from palm oil sludge (POS). POS is one of the most difficult and complex industrial waste produced in Malaysia from palm oil processing plants. Three different samples of POS were collected from different pond of Palm Oil effluent in palm oil processing plant in Sedenak, Kulai, Malaysia. The concentration of sulfate content in the samples were analysed in order to determine the sample that contain high population of bacteria capable of sulfate reduction. This ensures the possibility of isolating the bacteria of interest from the selected sample. Results from SRB-Bart kit analysis showed that POS from raw pond contain high population of SRB or related bacteria and was chosen for further isolation of the bacteria. Isolation of the bacteria was conducted using selective enrichment method followed by growth on solid medium using rolling bottle technique. The isolation has successfully separated five different pure culture coded X2 , X1, E, B and C that were further identified using the analysis of amplified 16S rRNA sequences of the individual bacterium. Four of the bacteria namely E, B, X1, and X2 were found able to reductively degrade sulfate. These bacteria were able to grow and reduce limited amount of sulfate thus indicated to the assimilatory reduction of sulfate activity of these bacteria.